Proposals for the Second Five Year Plan Scheduled Castes Vol. No. III Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
It has been, node clear win to proposing the creation of a post of a Regional assistant Organiser for the Administration of Welfare Schemes for the Scheduled Tribes, that unless staff necessary for supervising and execution of different schemes is appointed the success of the plan would not be guaranteed.
Government of Madhya Bharat